Meningkatkan Motivasi Belajar Al-Qur’an Surat At-Tin Siswa Kelas IV Melalui Model Cooperatif Learning SD Negeri 11 Magek - Inesri Inesri; Annisa Sri Lestari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Education is an important means of developing competitive human resources. However, the reality in the field shows that student motivation to learn, especially in Islamic Religious Education and Ethics subjects, is still low. This condition has an impact on suboptimal learning outcomes. One alternative solution is to apply the Cooperative Learning model, which encourages students to be active, work together, and build understanding in groups. This research is a Classroom Action Research (CAR) with a qualitative descriptive approach, conducted in class IV of SD Negeri 11 Magek with 31 students. The research instruments included student activity observation sheets, lesson plan assessments, learning implementation assessments, and learning outcome tests. Data analysis was conducted using qualitative and quantitative descriptive methods. The results showed a significant increase in student motivation and learning outcomes. In cycle I, the learning completeness level was only 47.62%, while in cycle II, it increased to 90.48%. Thus, the application of the Cooperative Learning model proved to be effective in increasing student learning motivation in the Q.S. At-Tin material.